Correlation between serum inflammatory factors and cognitive function in patients with high-altitude polycythemia: A case-control study - Li, Yinglan; Wang, Jiabing; Zhang, Xiuxin; Ye, Qiong; Yang, Yuan; Cui, Xiaoshan; Feng, Jinhua; Li, Jimei (Medicine (Baltimore), 2024)
The purpose of this study is to investigate the serum inflammatory factors in patients with high-altitude polycythemia (HAPC) and their correlation with cognitive function. The subjects were recruited and placed into a HAPC group and control group. Serum samples were collected, and inflammatory factors (interleukin-1beta [IL-1β], monocyte chemoattractant protein-1 [MCP-1], and tumor necrosis factor-alpha [TNF-α]) were measured using ELISA kits. The mini-mental State Examination (MMSE) was used to assess cognitive function. According to the MMSE scores, HAPC group was further divided into normal cognitive function group (HNCF) and cognitive dysfunction group (HCDF). In comparison with the control group, the MMSE scores in the HAPC group were significantly low (P < .05), whereas the serum levels of IL-1β, MCP-1, and TNF-α were significantly high (P < .01). Among the HAPC group (n = 60), 21 belonged to the HCDF and 39 belonged to the HNCF. Compared with the HNCF, the IL-1β, MCP-1, and TNF-α in the HCDF were significantly increased (P < .01). The Pearson correlation analysis showed that inflammatory factors were positively correlated with hemoglobin, and negatively correlated with MMSE. Serum inflammatory cytokines IL-1, MCP-1, and TNF-α were increased in HAPC, and HAPC exhibited cognitive dysfunction. Considering chronic hypoxia environment influences the change of the red blood cell metabolic and inflammatory factor, red blood cells and inflammatory factor in plateau is likely to be affected by patients with vascular lesions, increase cognitive impairment.